Gender stereotypes and gender portrayal in video games : the case of lol - Ioannou, Iraklis (Department of Multimedia and Graphic arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2016)
Video games are unquestionably an integral part of our lives: they offer entertainment, education, and socializing. Video games fulfill much more than they used to when they first appeared and are by far more prevalent in our everyday routine, especially since the appearance of handheld devices and mobile gaming. Despite popular beliefs, video games do not fail to attract people of all ages and genders. In fact, about 50% of gamers are women – a facet that is often disregarded by video game companies when pitching or designing new video games. Being such a huge source of information to a wide range of people–a range that excludes no one–video games have reasonably been studied extensively. Researches and critics raise controversial matters on video games’ content and uses. This thesis focuses on the case of gender portrayal, particularly how gender is generally represented in video games and what stereotypes prevail. This work uses the currently most popular video game, League of Legends, and its 130 playable characters (champions) as a case study, in an attempt to evaluate whether the game embraces or dismisses these gender stereotypes. Results show that the game does embrace certain gender stereotypes. Female champions are only as half as male ones and they are by far, more stereotypically depicted (skinny, small waists, large breasts, conventionally attractive) than men, whose appearances vary and often deviate from ideal standards of beauty. Female champions are also more likely to wear revealing and/or tight clothes, are generally younger, and are sometimes even promoted in certain ways so as to appeal through their bodies rather than skills or power, even though this is a fantasy strategy fighting game. The study provides guidelines for the design of stereotype-free video games and discusses implications of this work for future research and practice.
Keywords: Video games; Gender stereotypes; Gender portrayal; Gender representation; Character design; Sexism; League of Legends